1995
DOI: 10.1590/s0101-81751995000300023
|View full text |Cite
|
Sign up to set email alerts
|

Notas sistemáticas sobre Brassolinae: I. Tribos (Lepidoptera, Nymphalidae)

Abstract: Mirna l\1artins Cl'iagrande 2ABSTRACT. Sn-r"MATIC NOT"S AIIOI '1 BKASSOLlNAE. I. TKIIl"S (L"PII)(WI'''KA.Nnll'IIALlIlA"). A revis.:d dassificalion for lhe Neolrorical suhfamily Brassolinae hased on the ll1orphological sludy of seventy six of lhe eighty one kn<)w species (STI("II"1. 1932). divickd the suhfall1ily in lwolrihes. according lo lhe following lisl: Brassolini Boisduval. IX36 induding f,)rteen gene..,,, Bmssnlis Fahricius. I X07 (Iype genus): Coligo Hiihner. I XII}.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The determination of species was accomplished with the use of specialized bibliography (Le Moult and Real 1962;D'Abrera 1981;Ackery and VaneWright 1984;D'Abrera 1984;Otero 1986;D'Abrera 1987a;Ackery 1988;Blandin 1988;D'Abrera 1988;Brown Jr. 1992;Blandin 1993;D'Abrera 1994;Mielke 1994;Casagrande 1995;D'Abrera 1995;Canals 2003), or by comparison to those already deposited in the Collection of the Laboratory of Evolutionary Biology (Giovenardi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of species was accomplished with the use of specialized bibliography (Le Moult and Real 1962;D'Abrera 1981;Ackery and VaneWright 1984;D'Abrera 1984;Otero 1986;D'Abrera 1987a;Ackery 1988;Blandin 1988;D'Abrera 1988;Brown Jr. 1992;Blandin 1993;D'Abrera 1994;Mielke 1994;Casagrande 1995;D'Abrera 1995;Canals 2003), or by comparison to those already deposited in the Collection of the Laboratory of Evolutionary Biology (Giovenardi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent phylogenetic analyses have indicated that the Brassolini constitutes a monophyletic group (Brower, 2000; Freitas & Brown, 2004; Peña et al , 2006), which is not surprising given the past 170 years of research (e.g. Boisduval, 1836; Stichel, 1904; Fruhstorfer, 1912; Ehrlich, 1958; Ackery, 1988; Casagrande, 1995). The DNA‐based cladistic analysis by Peña et al (2006) examined a broader sample of taxa within the Satyrinae, Brassolini, Morphini and Amathusiini than ever before, thus strengthening the support for the Brassolini as a natural group, and suggesting that these three tribes are basal lineages within the Satyrinae.…”
Section: Introductionmentioning
confidence: 98%
“…Some adult characters present in Bia conflict with the traditional diagnosis for the Brassolini, whereas others are homoplasious. The following character state combination has been used to define the Brassolini: (1) closed hindwing discal cell; (2) absence of swollen veins; and (3) presence of a hindwing precostal cell (Casagrande, 1995). Freitas & Brown (2004) showed that the ‘closed hindwing discal cell’ is highly homoplasious within Nymphalidae, being gained independently and lost in various nodes of their tree.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations